An Early Adverse Experience Goes a Long, Criminogenic, Gendered Way: The Nexus of Early Adversities, Adult Offending, and Gender - Liu, Lin (Women & criminal justice, 2021)
Early adverse experiences have been identified as a salient risk factor for crime and delinquency. However, past empirical studies predominantly used youth and young adult samples; much less is known about this risk factor’s effect on adult offending. This study examines early adverse experiences and adult pro-social bonds simultaneously using a mixed-gender sample of serious adult offenders with an average age of 35. Findings from survival analysis suggest that early adversities have an enduring detrimental effect on people’s lives well into adulthood yet in an intricate way. They have no direct effect on recidivism among adult offenders. However, they significantly influence recidivism by interacting with gender: Female respondents with early adversities demonstrated a significantly higher risk of recidivism than other female respondents, whereas no such effect was observed among male respondents. Implications for future research and policymaking are discussed.